2017
DOI: 10.1128/aac.01293-17
|View full text |Cite
|
Sign up to set email alerts
|

A Quasi-Experiment To Study the Impact of Vancomycin Area under the Concentration-Time Curve-Guided Dosing on Vancomycin-Associated Nephrotoxicity

Abstract: Evidence suggests that maintenance of vancomycin trough concentrations at between 15 and 20 mg/liter, as currently recommended, is frequently unnecessary to achieve the daily area under the concentration-time curve (AUC 24 ) target of Ն400 mg · h/liter. Many patients with trough concentrations in this range have AUC 24 values in excess of the therapeutic threshold and within the exposure range associated with nephrotoxicity. On the basis of this, the Detroit Medical Center switched from trough concentration-gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
182
4
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 201 publications
(201 citation statements)
references
References 34 publications
13
182
4
2
Order By: Relevance
“…Recent studies have provided support for the AUC‐guided, Bayesian approach to dosing for vancomycin . Compared with trough‐based concentration targets, the AUC‐guided approach was shown to lead to decreased nephrotoxicity, reduced per‐patient blood sampling, and shorter length of therapy, while maintaining efficacy …”
Section: Integration Of the Auc/mic Ratio Into Clinical Practicementioning
confidence: 99%
“…Recent studies have provided support for the AUC‐guided, Bayesian approach to dosing for vancomycin . Compared with trough‐based concentration targets, the AUC‐guided approach was shown to lead to decreased nephrotoxicity, reduced per‐patient blood sampling, and shorter length of therapy, while maintaining efficacy …”
Section: Integration Of the Auc/mic Ratio Into Clinical Practicementioning
confidence: 99%
“…Clinical data examining the impact of AUC‐guided dosing are limited and not the focus of this article. One study included 1280 patients (734 underwent AUC‐guided dosing with collection of two levels and utilization of equation 4) and found that AUC‐guided dosing resulted in lower daily vancomycin doses and reduced risk of nephrotoxicity . In agreement with other data, a large percentage of patients had adequate AUC with troughs lower than 15 mg/L.…”
Section: Discussionmentioning
confidence: 67%
“…Patients with normal renal function would require doses between 3500 and 4500 mg/day to maintain the conventional target trough goal compared with doses between 2250 and 3250 mg when targeting goal AUC 24 . As demonstrated in previous studies, reduced vancomycin doses targeting AUC may minimize the potential for nephrotoxicity …”
Section: Discussionmentioning
confidence: 99%